2020
DOI: 10.1186/s12951-020-00700-8
|View full text |Cite
|
Sign up to set email alerts
|

Alpha lipoic acid antagonizes cytotoxicity of cobalt nanoparticles by inhibiting ferroptosis-like cell death

Abstract: As a main element in the hard metal industry, cobalt is one of the major components of human metal implants. Cobalt-containing implants, especially joint prostheses used for artificial joint replacement, can be corroded due to the complex physiological environment in vivo, producing a large number of nanoscale cobalt particles (Cobalt Nanoparticles, CoNPs). These CoNPs can be first accumulated around the implant to cause adverse local reactions and then enter into the blood vessels followed by reaching the liv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 68 publications
(96 reference statements)
1
28
0
Order By: Relevance
“…In turn, the lower pH associated with inflammation is a contributor to corrosion phenomena; the resulting increase in released particles will perpetuate inflammation, further implant structural damage, and eventually promote systemic effects ( Eliaz, 2019 ; Hameister et al, 2020 ). Ferroptosis is a form of controlled cell death that occurs in the presence of iron overload and leads to the formation of lipid ROS ( Sharma and Flora, 2021 ), and its association with peri-implant inflammation and cell death has been suggested ( Liu et al, 2020 ). Likewise, increased local ROS levels, inflammation and metallosis have been associated with titanium alloy implants and tribocorrosion phenomena ( Borys et al, 2019 ; Eliaz, 2019 ).…”
Section: Oxidative Stress and Orthopedic Implantsmentioning
confidence: 99%
“…In turn, the lower pH associated with inflammation is a contributor to corrosion phenomena; the resulting increase in released particles will perpetuate inflammation, further implant structural damage, and eventually promote systemic effects ( Eliaz, 2019 ; Hameister et al, 2020 ). Ferroptosis is a form of controlled cell death that occurs in the presence of iron overload and leads to the formation of lipid ROS ( Sharma and Flora, 2021 ), and its association with peri-implant inflammation and cell death has been suggested ( Liu et al, 2020 ). Likewise, increased local ROS levels, inflammation and metallosis have been associated with titanium alloy implants and tribocorrosion phenomena ( Borys et al, 2019 ; Eliaz, 2019 ).…”
Section: Oxidative Stress and Orthopedic Implantsmentioning
confidence: 99%
“…The excessive accumulation of ROS and the production of a large number of in ammatory cytokines such as TNF-α play an important role in the toxicity mechanism induced by cobalt nanoparticles, leading to in ammation, cell damage and proliferation, which in turn leads to DNA damage and DNA mutations, as well as damage to mitochondria, lysosomes and the nucleus, eventually leading to cell death. Past studies have found that although the apoptosis rate of treatment is signi cantly higher than that of the control group, it is still much lower than the cell death rate [28]. Therefore, it could be possible that there are still other types of cell death besides apoptosis in MG-63 cells exposed to CoNPs.…”
Section: Discussionmentioning
confidence: 91%
“…The appearance of abundant blue fluorescent aggregations was due to the absorbability of the CQDs, which could attract and enwrap neighboring particles. With the increasing CQD content, the blue fluorescence became stronger and more disordered, revealing that the bright PL emission of the CQDs formed from wood processing residues originated from their inherent carbon core of band gaps and extrinsic surface defects [ 30 ].…”
Section: Resultsmentioning
confidence: 99%